1891 N.H. Pub. Stat. 713 - (:unkn) unknown (My University, 1883)
Ch. 265, § 4: If any person shall have in his possession a toy pistol, toy revolver, or other toy firearms, for the explosion of percussion caps or blank cartridges, with intent to sell the same, or shall sell, or offer to sell or to give away the same, he shall be fined not more than fifty dollars
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES